Where’s the Bias: No Evidence of Bias by Sex When Testing the Public Safety Assessment - DeMichele, Matthew (Crime & delinquency, 2024)
Pretrial assessments are criticized for inherent biases. We conduct research in Kentucky to assess the predictive validity and differential prediction by sex of one pretrial assessment, the Public Safety Assessment (PSA). Our research is unique because we find equal base rates by sex for missing a court date, which allows us to assess for error rate balance by sex. We find the PSA to have predictive validity within acceptable ranges for the criminal legal field. The analyses show a lack of evidence of predictive bias for any arrest or missing a court date, and we find equal error rates for five different error measures. The analyses contribute to methodological debates about how to measure predictive bias with assessments.